Bilakah Kepala Daerah Tak Korupsi - Dedy Suhendi (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2020)
As it is known that many regional heads in several provinces as well as in districts and cities are not free from the problem of corruption. This may be due to the inaccuracy of the requirements for regent, mayor and governor candidates. This article considers it all an irony, because to lead the government in the regency area alone, a regent will later be side by side with the leadership of the vertical elements assigned to the area such as the Dandim, the police chief, the head of the district attorney and the head of the district court, even he will become the coordinator. We all know that positions in these vertical elements are not easy, they have to go through certain structural education levels so that it takes a relatively long time to reach a leadership position at the regional level.